Analisis preservasi amplitudo dan resolusi seismik pada data hasil reconvolution lapangan “X” Cekungan Sumatera Tengah - Agus Muhidin; Udi Harmoko; Hernowo Danusaputro; Moh. Irfan Saputra Haris (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Structure interpretation of post-stack seismic data to delineate lithology boundary sometimes face difficulties in tracking reflector continuity, this is due to limitation of vertical resolution. Reconvolution method has been applied to fix vertical seismic resolution. In order to validate the function reconvolution to amplitude related interpretation, amplitude variation with offset (AVO) has applied to geology model. Reconvolution method was applied by increasing dominant frequency of seismic data and capable to minimize tuning thickness zone of geology model has been made. Modeling geology based on average of P velocity, S velocity, and density from field “X” well data and estimating P velocity, S velocity and density for fluid condition of reservoir. AVO analysis has been applied to validate how far reconvolution method capable to maintain amplitude behavior, AVO analysis using Zeoppritz equation in 10 to 30 degree angle and using intercept attribute (A), gradient (B) and product (A*B). Reconvolution method has used 50 Hz, 60 Hz, 65 Hz, and 70 Hz of wavelet. Reconvolution method capable to fix vertical seismic data resolution, it can be seen by decreasing of tuning thickness from 16 to 14 meters. Based on AVO analysis that be used for validate reconvolution method is showing intercept (A) and gradient (B) value be affected by fluids condition in reservoir and presence the random noise in the seismic data. Intercept (A) and gradient (B) for reconvolved data do not have significant changes. However, wavelet has used in reconvolution that possess the smallest error value is wavelet with dominant frequency in 60 Hz and 65 Hz.Keywords: Structure interpretation, Tuning thicknes, Recovolution, and AVO analysis.